Growth and yield of strawberry cultivars (Fragaria sp.) affected by flooding - Casierra-Posada, Fánor; Vargas, Yuber A. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
In general, the excess of water has a negative impact on growth and survival of most terrestrial plants, especially when flooding occurs during the growing season. In a pot experiment, the production and distribution of dry matter, specific leaf weight, root to shoot ratio, total harvested fruit, normal and necrotic leaf area, plant harvest index and pH of soil after flooding were measured in three strawberry cultivars. Plants were grown in flooded and a non-flooded soil (control). The tested cultivars were Chandler, Camarosa and Sweet Charlie. This work was carried out in a greenhouse in Tunja, Colombia. As a consequence of flooding, the pH of soil, specific leaf weight, necrotic leaf area and root/shoot ratio increased, whereas the harvested fruit, total dry matter production and total leaf area decreased. Flooding also affected the distribution of dry matter in the tested cultivars, with the Chandler cultivar being the most affected. In general, the strawberry plant demonstrated poor behaviour when exposed to flood conditions.